KOMPETENSI DAN PENGETAHUAN NURSING INFORMATICS DALAM PENGGUNAAN ELECTRONIC HEALTH RECORD: A LITERATURE REVIEW - Sri Agustin Tabara; La Ode Abdul Rahman; Tri Mulia Herawati (Institut Kesehatan Hermina, 2023)
Industry 4.0, information technology has influenced all sectors, including nursing. The developing information technology that has been used by health services, namely hospitals throughout the country, is Electronic Health Records (EHR). The users with the largest number of users who use EHR are nurses. So, nurses need to have the ability to use EHR which is called Nursing Informatics (NI). There are 5 journals used in this literature review. The results obtained were that NI helped nurses in using the EHR. NI competency requires nurses to be able to use computers. To be able to maximize the use of computers, nurses need to understand informatics so that they can use the EHR optimally.